ANALYSIS OF GENERAL ALLOCATION FUND EFFICIENCY AND REGIONAL ORIGINAL INCOME ON THE FINANCIAL PERFORMANCE OF CITY GOVERNMENTS IN PROVINCE ACEH - Malinda Sari; Ichsan Ichsan (Journal of Malikussaleh Public Economics, 2020)
This study aims to analyze the efficiency of general allocation funds (DAU) and local own-source revenues (PAD) on the financial performance of city governments in Aceh Province. The data used in this study is panel data, which includes input variables of general allocation funds, regional original income and output variables of financial performance in 2015-2018. The method used in this research is Data Envelopment Analysis (DEA) using DEAP software version 2.1. The analysis shows that in 2015 there were 4 cities that experienced efficient, namely Banda Aceh City, Sabang City, Langsa City and Subulussalam City, in 2016 there were 4 cities that showed efficient, namely Banda Aceh City, Sabang City, Langsa City and Kota Subulussalam, In 2017, the number of cities that showed efficient was 4 cities, namely Banda Aceh City, Langsa City, Lhokseumawe City and Subulusalam City, while in 2018, there were 5 cities that showed efficient, namely Banda Aceh City, Sabang City, Langsa City, Lhokseumawe City and Subulussalam City. To improve its financial performance, the city governments in Aceh Province, especially those whose financial performance has not reached the level of efficiency should make a draft budget in accordance with regionalKeywords: public Financial Performance, Local Revenue, General Allocation Funds, Data Envelopment Analysis